Matefin/SUN-1 phosphorylation is part of a surveillance mechanism to coordinate chromosome synapsis and recombination with meiotic progression and chromosome movement. - Alexander Woglar; Anahita Daryabeigi; Adele Adamo; Cornelia Habacher; Thomas Machacek; Adriana La Volpe; Verena Jantsch (PLoS Genetics)
Faithful chromosome segregation during meiosis I depends on the establishment of a crossover between homologous chromosomes. This requires induction of DNA double-strand breaks (DSBs), alignment of homologs, homolog association by synapsis, and repair of DSBs via homologous recombination. The success of these events requires coordination between chromosomal events and meiotic progression. The conserved SUN/KASH nuclear envelope bridge establishes transient linkages between chromosome ends and cytoskeletal forces during meiosis. In Caenorhabditis elegans, this bridge is essential for bringing homologs together and preventing nonhomologous synapsis. Chromosome movement takes place during synapsis and recombination. Concomitant with the onset of chromosome movement, SUN-1 clusters at chromosome ends associated with the nuclear envelope, and it is phosphorylated in a chk-2- and plk-2-dependent manner. Identification of all SUN-1 phosphomodifications at its nuclear N terminus allowed us to address their role in prophase I. Failures in recombination and synapsis led to persistent phosphorylations, which are required to elicit a delay in progression. Unfinished meiotic tasks elicited sustained recruitment of PLK-2 to chromosome ends in a SUN-1 phosphorylation-dependent manner that is required for continued chromosome movement and characteristic of a zygotene arrest. Furthermore, SUN-1 phosphorylation supported efficient synapsis. We propose that signals emanating from a failure to successfully finish meiotic tasks are integrated at the nuclear periphery to regulate chromosome end-led movement and meiotic progression. The single unsynapsed X chromosome in male meiosis is precluded from inducing a progression delay, and we found it was devoid of a population of phosphorylated SUN-1. This suggests that SUN-1 phosphorylation is critical to delaying meiosis in response to perturbed synapsis. SUN-1 may be an integral part of a checkpoint system to monitor establishment of the obligate crossover, inducible only in leptotene/zygotene. Unrepaired DSBs and unsynapsed chromosomes maintain this checkpoint, but a crossover intermediate is necessary to shut it down.